SIMULASI SMART HOME IOT DENGAN APLIKASI CISCO PACKET TRACER - lim, sheren; Wijaya Massie, Alamsyah; Yanto, Endri; Huang Wijaya, Jacky; Pernando, Yonky (Fakultas Komputer - Universitas Universal, 2025)
This study was conducted with the aim of simulating an IoT-based smart home system by utilizing the Cisco Packet Tracer version 8.2.2. This simulation application is used because it is able to provide a network simulation environment that is close to the real world to understand the basic concepts of IoT and its application in smart home systems. The method used in this study is the system development and simulation approach, where researchers design a smart home network consisting of several devices, such as fans, air conditioners, lights, windows, webcams, and garage doors. All of these devices are configured to be controlled automatically via sensors and manually remotely using a cloud-based interface. The results of this study's simulation show that all predetermined devices have been successfully integrated and controlled properly according to the previously designed scenario. Cisco Packet Tracer shows effective results in visualizing the workflow of an IoT-based smart home system and allows stable network communication between devices.